The drag reduction and degradation characteristics of poly α olefin in diesel via rotating disk apparatus. (3rd July 2018) - Dai, Xiaodong; Li, Lei; Yin, Shuming; Zhang, Guicai; Ge, Jijiang
ABSTRACT: Poly α olefin/diesel system was studied by experiments with a rotating disk apparatus, to investigated drag reduction and degradation behavior. Four different concentrations were tested with time, rotating speed, temperature, mechanical and ultrasound treatment. The results show that there is a optimum time and maximum DR% for drag reduction, and DR% increases slowly with temperature in diesel. The higher concentration possesses shorter optimum time but higher rotating speed to take effect. Also higher DRA concentration shows better degradation resistance at intensive shear and ultrasound circumstance. This phenomenon could be attributed to poly α olefin prefer to form more clusters than single molecule forms at high concentration, comparing with lower one.